Monetary Policy Of Developing Countries In Inflationary Processes - et. al., Dr. Mardanova Rano Isakovna , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines the issue of inflationary processes, in which the macroeconomic situation in developing countries is in a deplorable state, when the state is faced with the choice of active application of two macroeconomic policies, this is either fiscal policy or monetary policy. The purpose of this article is to consider macroeconomic stability from the point of view of monetary policy, since the state budget deficit that has arisen in the economy requires an optimal combination, as well as the introduction of the right financial instruments. Thus, the article focuses on the macroeconomics of developing countries, and then considers the theory of eliminating inflationary processes. A detailed theoretical analysis is provided, strengths and weaknesses of monetary policy are indicated, its application in practice to developing countries with a small open economy based on the short and long term aspects. Several options are being considered to eliminate inflationary processes. Monetary policy is examined in detail. The positive impact of devaluation on the country's economy, as well as a brief overview of the monetary policy of the PRC to eliminate inflationary processes, the experience of China in attracting foreign currency, that is, capital inflow, is considered. The purpose of this article is to show the ways of solving inflationary processes that arise in developing countries applying an active monetary policy